Changes in Vertical Mobility of the First Tarsometatarsal Joint During Gait After Combined Hallux Valgus Surgery Incorporating Proximal First Metatarsal Osteotomy - Yasunari Ikuta; Tsubasa Tashiro; Noriaki Maeda; Satoshi Arima; Honoka Ishihara; Sakura Oda; Yuki Tamura; Saori Ishibashi; Satoru Sakurai; Dan Moriwaki; Tomoyuki Nakasa; Nobuo Adachi (Journal of Clinical Medicine, 2026)
Background/Objectives: Although proximal first metatarsal osteotomy is a common treatment for hallux valgus (HV), its effect on dynamic first tarsometatarsal (TMT) joint mobility remains unclear. Previous assessments have largely relied on static radiographic parameters, which may not capture functional joint kinematics. The aim of this study was to evaluate changes in first TMT joint mobility during the stance phase of gait using a synchronized ultrasound and three-dimensional motion capture system after combined hallux valgus surgery incorporating proximal first metatarsal osteotomy. Methods: We prospectively studied 23 feet of 21 female patients with symptomatic HV undergoing combined hallux valgus surgery incorporating proximal closing-wedge osteotomy. We also evaluated 11 feet of 11 healthy female volunteers as controls. Per clinical indications, additional concomitant procedures were performed for 21 of the 23 feet. Vertical displacement of the first metatarsal and medial cuneiform as well as the first TMT joint gap was measured throughout the stance phase of gait using a synchronized ultrasound and motion capture system. Pre- and postoperative kinematics (>1 year follow-up) were compared with those in the control group using one-dimensional statistical parametric mapping (SPM). Results: Radiographically, the HV and intermetatarsal angles significantly improved, while sagittal plane parameters showed no significant changes. SPM analysis revealed no significant differences in the first TMT joint gap or first metatarsal displacement among groups. Preoperatively, compared with the controls, HV feet exhibited significantly greater plantar displacement of the medial cuneiform during late terminal stance. Postoperatively, this abnormal displacement was significantly decreased, with no significant difference between groups. Conclusions: Combined hallux valgus surgery incorporating proximal first metatarsal osteotomy was associated with reduced dynamic medial column hypermobility, specifically shifting vertical displacement of the medial cuneiform towards patterns observed in healthy controls during the terminal stance phase. These functional improvements occurred despite minimal changes in static sagittal radiographic alignment. The findings highlight the importance of dynamic assessment for evaluation of postoperative medial column biomechanics.